The problems of siri marriage for couples who have not married according to the law in marriage legal perspective - Idris Idris; Raya Lestari; Zetria Erma (LEGAL BRIEF, 2023)
The purpose of this research is to find out the problems that occur in couples who are not legally married according to the law in the perspective of marriage law in Indonesia. The type of research in this paper is normative with a statutory and conceptual approach. While the specification of the research is analytical descriptive, namely explaining the problem according to the research title. The data used is secondary data consisting of primary legal materials in the form of Law no. 1 of 1974, KHI (Compilation of Islamic Law), and secondary legal materials in the form of books, journals and writings related to research titles. The problem for anyone who enters into a marriage even though it is with religiously valid pillars and conditions but not registered causes more disadvantages than advantages. As a result of unregistered marriages, there will be difficulties in processing important letters as administrative requirements in civil affairs. In addition, it is not legally recognized because it does not give rise to civil relations as husband and wife.